Cryopreservation media differentially affect sperm motility, morphology and DNA integrity. (13th August 2018) - Raad, G.; Lteif, L.; Lahoud, R.; Azoury, J.; Azoury, J.; Tanios, J.; Hazzouri, M.; Azoury, J.
Abstract: Introduction: Human sperm freezing is very widely used for male fertility preservation. This procedure consists in adding cryoprotectants to the spermatozoa followed by cooling and storing the spermatozoa at a subzero temperature. Many standardized cryopreservation media are available on the market. However, these media differ in their chemical composition and there are no sufficient data to optimize their classification. Therefore, the aim of this study was to compare five commercially available sperm cryopreservation media, which have not been compared together, in terms of motility, morphology and DNA integrity. Materials and methods: One‐hundred semen samples were obtained from 10 fertile participants and 90 infertile men. Each sample was evaluated before freezing for motility, morphology and DNA fragmentation index (DFI). Then, it was equally divided into five aliquots. Each aliquot was cryopreserved using one of the five media (A, B, C, D, and E). The same parameters were re‐evaluated after the addition of the cryopreservation media in the fertile group, and after sperm thawing in fertile and infertile groups. Results: The results showed that the five selected cryopreservation media had negative effects on sperm motility and morphology per se. In the infertile group, the cryosurvival factor was significantly lower in cryomedium A when compared to the four other media ( p < 0.001). In addition, a significantly higher percentage of sperm with coiled tail was detected in cryomedium E compared to cryomedium A ( p < 0.05) and to cryomedium B ( p < 0.001) after thawing, in the infertile group. Furthermore, the sperm DFI was significantly higher in cryomedia A ( p < 0.001), B ( p < 0.001), C ( p < 0.01), D ( p < 0.01) and E ( p < 0.05) compared to that of the fresh semen derived from infertile participants. Conclusion: This study indicates that the recovery rate of competent spermatozoa, after cryopreservation, is still critical in infertile men. Therefore, frozen semen sample should be used only when necessary.